Inovasi Pelatihan Penggunaan Aplikasi Educaplay Untuk Guru Di SMP Negeri 5 Katingan Tengah Dalam Meningkatkan Kualitas Pembelajar Siswa - Yedithia, Fenroy; Setiawati, Nani; Damayanti, Indri (Early Childhood Research and Practice, 2025)
Recent technological developments have brought significant changes in various fields, including education. Teachers are required to innovate in creating engaging and student-centered learning experiences. This study aims to describe the impact of Educaplay application training on improving the quality of learning at SMP Negeri 5 Katingan Tengah. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that Educaplay training has a positive impact on teachers' competencies in developing diverse and interactive learning materials. Students also showed high levels of interest and enthusiasm during the learning process. This platform not only facilitates teachers in delivering materials but also encourages active student participation, increases learning motivation, and develops critical and creative thinking skills. Thus, the use of Educaplay has proven effective in supporting the improvement of digital-based learning quality.